“Saya Tidak Mau Ikut Demonstrasi”: Collective Action terhadap Procedural Injustice Ditinjau dari Empat Tipologi Budaya - Akhmad Saputra Syarif; Amya Bunga Fathiyah; Fadhilatussyifa Auliyarahmani Bahtiar; Fajriah Rahmah B Arafah; Nadhifa Annisa Rosalinda (UIN Sunan Kalijaga, 2025)
This study aims to examine whether cultural typologies: vertical collectivism (VC), horizontal collectivism (HC), vertical individualism (VI), and horizontal individualism (HI), predict individuals’ intentions to engage in collective action in response to procedural injustice. The study employed a quantitative survey design involving 300 participants (67.67% female; 89% aged 18–30 years). Participants were presented with a procedural injustice vignette and subsequently completed the Individualism–Collectivism Scale (Triandis & Gelfand, 1998) and the Belief-Aligned Collective Action Scale (Cervone et al., 2023). Data were analyzed using multiple linear regression while controlling for age and gender. The findings indicate that vertical individualism significantly predicts higher intentions to engage in collective action (p < .001), whereas other cultural typologies do not show significant effects. These results suggest that individualistic orientations emphasizing competition and status differentiation may play a stronger role in motivating collective action under conditions of procedural injustice. Penelitian ini bertujuan untuk menguji peran tipologi budaya; vertical collectivism (VC), horizontal collectivism (HC), vertical individualism (VI), dan horizontal individualism (HI), dalam memprediksi intensi individu untuk terlibat dalam aksi kolektif ketika menghadapi ketidakadilan prosedural. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei yang melibatkan 300 partisipan (67,67% perempuan; 89% berusia 18–30 tahun). Partisipan terlebih dahulu diberikan skenario ketidakadilan prosedural (vignette), kemudian diminta mengisi Individualism–Collectivism Scale (Triandis & Gelfand, 1998) dan Belief-Aligned Collective Action Scale (Cervone et al., 2023). Data dianalisis menggunakan regresi linier berganda dengan mengontrol variabel usia dan jenis kelamin. Hasil analisis menunjukkan bahwa hanya tipologi budaya vertical individualism yang secara signifikan memprediksi peningkatan intensi aksi kolektif (p < .001), sementara tipologi budaya lainnya tidak menunjukkan pengaruh yang signifikan. Temuan ini mengindikasikan bahwa orientasi individualistik yang menekankan kompetisi dan diferensiasi status memiliki peran yang lebih kuat dalam mendorong aksi kolektif dalam konteks ketidakadilan prosedural.